Gastric Inflammatory Fibroid Polyp in Children - Badriul Hegar; Tatang Puspanjono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Inflammatory fibroid polyp (IFP) constitutes as a chronic inflammatory lesion that is generally located in the gastric (gastric inflammatory fibroid polyp). The lesion originates from the submucosal tissue of the gastrointestinal tract and progress into a polypoid mass. Inflammatory fibroid polyp is rarely found in children and the cause is not definitely known. A case of a four-year old boy with recurrent paleness for 3 months has been reported. At the beginning, the patient was suspected of haemolytic anaemia. Except the hemoglobin level ( 5 g/dL), other laboratorium examination did not support the working diagnosis. During the last one months period, the patient also complained of recurrent abdominal pain and vomiting. On the abdominal ultrasonography (USG) and endoscopy, a mass that covered most of the gastric lumen was detected. Based on that finding, gastrectomy and mass removal were conducted. The pathologic anatomy examination proved the presence of an inflammatory fibrous polypoid. Follow-up untill 12 months showed no any complaint and abnormalities on endoscopic examination. Since there was no consensus regarding the follow-up period following the procedure, the evaluation of this patient would be conducted every 2-3 years. Keywords: inflammatory fibroid polyp, tumor, gastric, children